Caracterização metamórfica das rochas granulíticas de Chorozinho-CE - Soares, Wollker Cunha (2016)
The metamorphic evolution of granulite terrains are an intense research mark in the last few decades since, mostly, represent inferior and middle continental crust segments. Thereby, Chorozinho’s region (Ceará’s northeast) exhibits an granulite rock sequence which doesn’t have age determination and regional metamorphism studies, preventing a better understanding of an important region for the Ceará state geological contex. The main objective of this work is to find the protolith age and also determine pressure and temperature conditions for the major outcropping geological units representative lithotypes. The methodology applied in this work followed four differentiated stages, being bibliographical survey, field campaign, laboratorial stage, where the samples went through petrographic, geochronological (SHRIMP) and mineral chemistry (ICP-MS) analysis, and office stage. Chorozinho’s region possess three lithotypes: enderbitc gneiss, sillimanite-garnet-gneiss (diatexite) and biotite-gneiss. The first is an orthoderived rock and presents these identified minerals in thin section: plagioclase, K-feldspar, quartz, clino and orthopyroxene, hornblend, biotite ± garnet ± sphene ± zircon ± apatite ± opaque, in granoblastic texture, while the other two are paraderived. Sillimanite-garnet-gneiss (diatextite) have K-feldspar, quartz, plagioclase, sillimanite, biotite ± opaque ± garnet ± apatite ± zircon, as the biotite-gneiss have plagioclase, K-feldspar, quartz, biotite ± zircon ± apatite ± opaque, may have or not garnet, and both retain granolepidoblastic texture. The mineral chemistry shows that the garnet composition is mainly almandine, orthopyroxene is enstatite, clinopyroxene are augite and diopside, plagioclase proved to have an oligoclase-andesine composition (high metamorphic grade feature) and alkaline feldspar with sanidine composition. Biotite shown a flogopite/eastonite, rich FeO and TiO2, tendency. Relative to the region metamorphic conditions, the softwares, TWEEQU and THERMOCALC, revealed temperature between 700°C-790°C and pressure among 4-11,6 kbar, for the enderbitc gneiss. And so, U-Pb isotopic data, in zircon, aiming to define the protolith age, provided the expected information because the proximity with others ages, around 2,1-2,0 Ga.